2012
DOI: 10.4236/ajps.2012.312204
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity Assessment of Acid Lime (<i>Citrus aurantifolia</i> Swingle) Landraces in Nepal, Using SSR Markers

Abstract: Acid lime (Citrus aurantifolia) is an important commercial fruits crop, cultivated in terai to high hills of Nepal. High variation of acid lime fruits are observed in existing landraces due to crossing within the other citrus species. Determination of genetic variation is important to the plant breeders for development of high yielding variety and hybrids. Therefore, an attempt has been made to study the genetic diversity of 62 acid lime landraces, collected from different altitudinal range in the eastern part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 36 publications
7
16
0
Order By: Relevance
“…In our present investigation, the Terai. The result is comparable with the result obtained using SSR markers where accessions from high and mid-hills have the high average genetic similarity (73% and 81%) in comparison to Terai (69%) [39]. Our results showed that the collected accessions from different agro-ecological zones were not genetically distinct but highest diversity was observed in Terai accessions compared to in High and Mid-hills.…”
Section: 1issr Polymorphism and Genetic Diversity Estimation In Nesupporting
confidence: 84%
See 4 more Smart Citations
“…In our present investigation, the Terai. The result is comparable with the result obtained using SSR markers where accessions from high and mid-hills have the high average genetic similarity (73% and 81%) in comparison to Terai (69%) [39]. Our results showed that the collected accessions from different agro-ecological zones were not genetically distinct but highest diversity was observed in Terai accessions compared to in High and Mid-hills.…”
Section: 1issr Polymorphism and Genetic Diversity Estimation In Nesupporting
confidence: 84%
“…Accessions (LS-56, LS-57and LD-58) from Terai ecological zone are clustered together, similar to the results obtained in SSR-based phenogram by [39], indicating their genetic closeness. The intermixing of accessions that are grown in different agro-ecological domains in different clusters in the phenogram may be attributed to the genetic similarities among different accessions in various qualitative and quantitative traits.…”
Section: 1issr Polymorphism and Genetic Diversity Estimation In Nesupporting
confidence: 79%
See 3 more Smart Citations